Pengaruh Variasi Kedalaman Settling Pond terhadap Efektivitas Pengendapan TSS pada Tambang Nikel PT. Daka Group - A Fani Anugrah Tamar; Dian Dwi Apriliyani Arsdin; Tri Andriani HS. Kandora; Syarifullah Bundang; Apriadi Saputra (Journal of Applied Geoscience and Engineering, 2026)
A settling pond is an important facility in mining operations used to remove suspended solid particles so that wastewater quality complies with environmental standards. This study aims to analyze the effect of settling pond depth variations on flow velocity and TSS (Total Suspended Solids) removal efficiency at the settling pond of PT. Daka Group, North Konawe Regency, Southeast Sulawesi. The research methods included primary and secondary data collection, hydrological analysis, TSS testing, and Computational Fluid Dynamics (CFD) simulation using ANSYS Fluent. A pond depth of 2 m was used as the existing condition, while a depth of 3 m was evaluated as an alternative scenario to assess potential improvements in TSS removal performance and to provide recommendations for pond design optimization. The results showed a design rainfall of 80 mm/day, rainfall intensity of 11.65 mm/hour, and a maximum runoff discharge of 0.82 m³/s. Laboratory analysis indicated that the outlet TSS concentration was 53 mg/L, which met the applicable environmental quality standards. CFD simulation results demonstrated that the 3 m deep pond produced a more stable flow pattern and lower flow velocity than the 2 m deep pond. Based on Stokes’ Law calculations, the 3 m depth was more effective in removing TSS, with a sediment accumulation volume of 165.43 m³/day and a sediment dredging interval of 23 days. These findings indicate that increasing the pond depth to 3 m has the potential to improve TSS removal efficiency and can be recommended for optimizing mine water management.